Ethics of Conservation Triage - Wilson, Kerrie A.; Law, Elizabeth A. (Frontiers in Ecology and Evolution, 2016)
Conservation triage seems to be at a stalemate between those who accept triage based on utilitarian rationalization, and those that reject it based on a number of ethical principles. We argue that without considered attention to the ethics of conservation triage we risk further polarization in the field of conservation. We draw lessons from the medical sector, where triage is more intuitive and acceptable, and also from disaster planning, to help navigate the challenges that triage entails for conservation science, practice, and policy. We clarify the consequentialist, deontological, and virtue ethical stances that influence the level of acceptance of triage. We emphasize the ethical dimensions of conservation triage in principle and in practice, particularly in the context of stakeholder diversity, a wide range of possible objectives and actions, broader institutions, and significant uncertainties. A focus on a more diverse set of ethics, more considered choice of triage as a conservation tool, open communication of triage objectives and protocols, greater consideration of risk preferences, and regular review and adaptation of triage protocols is required for conservation triage to become more acceptable among diverse conservation practitioners, institutions, and the general public. Accepting conservation triage as fundamentally an ethical problem would foster more open dialogue and constructive debate about the role of conservation triage in a wider system of care.